Activity of hypothalamus-pituitary-thyroid axis in rats of different ages after long-term cold exposure - Lomako, Viktoria; Shylo, Oleksandr; Lutsenko, Dmytro; Lomako, Svitlana (Problems of Cryobiology and Cryomedicine, 2026)
Probl Cryobiol Cryomed. 2026;36(1):66—68